Strain INRA1077 (France) - Bolet G.; Saleil G. (Rabbit genetic resources in Mediterranean countries, 2002)
Strain selected for 30 generations for litter size at weaning, and now for litter size at birth and weight at 9 weeks. Used as grand-parental female strain to produce a parental crossbred female (INRA1077 ´ INRA2066 or other commercial strains), which is the most common parental female in France.